How knowledge on land values influences rural-urban development processes - Emília Malcata Rebelo (2008)
This paper stresses how important knowledge of land and real estate values, their underlying variables and valuation processes, as well as control over surplus-values generation and distribution, are for successful regional and urban planning. It discusses relations between rural and urban land, makes an analysis of the different components that underlie land value, interdependencies between land and real estate (real or potential) values, temporal perspectives of land use change, and behaviour of agents involved in development processes. Furthermore, an empirical methodology is presented in order to compute land surplus values. Conclusions are drawn concerning the implications of this analysis for regional and urban planning. The methodology set forth is expected to support better planning decisions concerning a balanced rural-urban development, thus fuelling a stronger sustainability of rural areas.